The role of brown adipose tissue in the calorigenic effect of adrenaline and noradrenaline in cold-acclimated rats - Himms-Hagen, Jean (1969)
1. Removal of the interscapular brown adipose tissue of the cold-acclimated rat has no immediate effect on the calorigenic response of the rat to adrenaline or noradrenaline. 2. There is a progressive loss of the enhanced response to adrenaline and to noradrenaline during the 4 days following removal of the interscapular brown adipose tissue from cold-acclimated rats. There is no loss of response in sham-operated cold-acclimated rats. 3. Removal of the interscapular brown adipose tissue from rats living at room temperature has no effect on the calorigenic response to adrenaline or noradrenaline, neither immediately afterwards nor 2-4 days later. 4. It is concluded that interscapular brown adipose tissue is not the major site of oxygen consumption in the enhanced calorigenic response to adrenaline or noradrenaline in cold-acclimated rats. However, it does play an important role in this enhanced metabolic response, probably as an endocrine gland whose secretory product modifies the ability of other tissues to respond calorigenically to catecholamines.